Legal Guarantees for Public Servants In The Face Of Disciplinary Penalties In Accordance With Iraqi Legislation - SalimLhaimus, Mohammed; Mohammed, QaysJasim (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of referring the offending public employee or accused of committing disciplinary offenses to the administrative investigation is to ensure the administration’s right to reveal the truth about the charges attributed to the accused employee regarding his commission of disciplinary offenses affecting the public interest of the administration, and if those violations are proven, then the administration has the right to punish the accused employee In accordance with the penalties stipulated in the Discipline Law of State and Public Sector Employees No. 14 of 1991 amended in accordance with Iraqi legislation, and at the same time, the legislator has provided many guarantees, including previous and contemporary, regarding disciplinary sanctions, including guarantees subsequent to imposing disciplinary penalties, and the purpose of these guarantees is not to abuse the administration in The use of the authority of punishment and that the penalties be proportional in terms of their material and moral effects to the size of the violations committed and that these guarantees are sufficient to achieve justice and reassurance for both parties, whether the administration or the employee is accused. Therefore, the study dealt with this topic according to a plan divided into two researches. Notifying the employee of the violations attributed to him, and then we dealt with contemporary guarantees And represented by the impartiality of the investigation authority, causing the punishment and guaranteeing the right of defense for the employee who is referred to the investigation. In the second section, we referred to guarantees subsequent to disciplinary punishment, represented by administrative grievance and judicial appeal against the disciplinary penalty decision in terms of the competent judicial authority to consider the appeal, procedures, and reasons for appeal.